2015
DOI: 10.1039/c4dt02292k
|View full text |Cite
|
Sign up to set email alerts
|

Acidity enhancement of unsaturated bases of group 15 by association with borane and beryllium dihydride. Unexpected boron and beryllium Brønsted acids

Abstract: The intrinsic acidity of CH 2 vCHXH 2 , HCuCXH 2 (X = N, P, As, Sb) derivatives and of their complexes with BeH 2 and BH 3 has been investigated by means of high-level density functional theory and molecular orbital ab initio calculations, using as a reference the ethyl saturated analogues. The acidity of the free systems steadily increases down the group for the three series of derivatives, ethyl, vinyl and ethynyl. The association with both beryllium dihydride and borane leads to a very significant acidity e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 53 publications
(58 reference statements)
0
13
0
Order By: Relevance
“…Recently, Manuel Yáñez et al [17][18][19][20][21][22][23] has substantiated the existence of another kind of noncovalent weak interactions, namely, beryllium bonds, which may have some significant implications in different fields. It is well established that the association of beryllium fluoride to ADP inhibits protein action.…”
Section: Introductionmentioning
confidence: 97%
“…Recently, Manuel Yáñez et al [17][18][19][20][21][22][23] has substantiated the existence of another kind of noncovalent weak interactions, namely, beryllium bonds, which may have some significant implications in different fields. It is well established that the association of beryllium fluoride to ADP inhibits protein action.…”
Section: Introductionmentioning
confidence: 97%
“…[26][27][28] By combination of one or more Lewis acids such as BeX 2 , BX 3 (X = H, F, Cl, Br), AlF 3 , AuF 5 , and SbF 5 with a Brønsted inorganic acid, strong acids are obtained. [29][30][31][32][33][34][35][36] The magic acid, (SbF 5 + HSO 3 F), [11] and SbF 5 + HF, with ΔG acid of 260.5 kcal mol −1 , [37] are well known examples of this category. Also, acidity assessment of superhalogens has shown that these compounds can act as inorganic superacids.…”
mentioning
confidence: 99%
“…[38,39] Other than inorganic superacids, acidity enhancement in the organic compounds due to interaction with Lewis acids such BX 3 , BeX 2 , AlX 3 , and MgX 2 has been studied both theoretically and experimentally. [34,[40][41][42][43][44][45][46] Interaction with Lewis acids may change organic bases into organic strong acids. For instance, interaction of BH 3 with amines leads to acidity enhancement from 40 to 47 kcal mol −1 [41] and its interaction with methyl phosphine enhances its acidity by about 29 kcal mol −1 .…”
mentioning
confidence: 99%
“…C 2015 Wiley Periodicals, Inc. Heteroatom Chem. Beryllepin is best described as a planar singlet heterocyclic conjugated triene with marginal aromatic character containing a C-Be-C moiety forced to be nonlinear (ࢬC-Be-C = 146.25°) by the cyclic constraints of the sevenmembered ring.…”
mentioning
confidence: 99%
“…Of the remaining nine beryllium-inserted benzenes, with the exception of the 11-membered ring containing five beryllium atoms and the 12-membered ring containing six beryllium atoms, which were calculated to exist as a ground state pentet and septet, respectively, all were calculated to be ground state triplet systems. C 2015 Wiley Periodicals, Inc. Heteroatom Chem. 27:37-43, 2016; View this article online at wileyonlinelibrary.com.…”
mentioning
confidence: 99%